ANALYSIS OF CLOVE LEAF OIL REFINING BUSINESS INCOME IN SIBALUTON VILLAGE, BASIDONDO DISTRICT: ANALISIS PENDAPATAN USAHA PEMURNIAN MINYAK DAUN CENGKEH DI DESA SIBALUTON, DISTRIK BASIDONDO - Moh. Nasir Dg Marumu; Joko Prathomo; Sri Wahyuni (International Journal of Economic Entrepreneurship and Business Management, 2024)
This study aims to find out how much Clove Leaf Oil Distillation Business Income in Sibaluton Village, Basidondo District (Case Study of Hasril Clove Leaf Oil Distillation). This study uses a qualitative research design. The data source is in the form of primary data, namely data obtained from the results of interviews and documentation related to this research. The data analysis methods used are qualitative and quantitative descriptive, namely production cost analysis, revenue analysis, income analysis, and cost revenue analysis (R/C Ratio). Based on the results of research and discussion, it shows that the total cost incurred by the Clove Leaf Oil Refining Business in Sibaluton Village, Basidondo District (Case Study of Hasril Clove Leaf Oil Refining) in running its business during 2023 is Rp. 155,532,000 and revenue is Rp. 211,200,000. This shows that the revenue of the clove leaf oil refining business for 1 year is Rp. 55,668,000 and the feasibility of the clove leaf oil refining business is the receipt of the R/C Ratio cost of 1.35. So, this shows that more than one means that the Clove Leaf Oil Distillation Business in Sibaluton Village, Basidondo District (Case Study of Hasril Clove Leaf Oil Distillation) is worth trying.